1977
DOI: 10.1113/jphysiol.1977.sp011733
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotrophin secretion in the ovariectomized guinea‐pig: effects of electrical stimulation of the hypothalamus and of LH‐RH.

Abstract: SUMMARY1. Serial blood samples were collected from anaesthetized spayed guinea-pigs subjected to anterior hypothalamic stimulation or injected with luteinizing hormone-releasing hormone (LH-RH), and the effect on the secretion of follicle-stimulating hormone (FSH) and LH followed.2. Hypothalamic stimulation enhanced LH secretion, although the response waned during the course of the 1 hr period of stimulation; the secretion of FSH was not increased. After stimulation, FSH and LH levels fell below control values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

1978
1978
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…14 17, 26], rabbit [25], guinea-pig [12], ferret [II], pig [4] and monkey [38] has been shown to influ ence levels of plasma luteinising hormone (LH). We have been studying in the anaesthetised cat the neurophysiology of some of these limbic connections which are involved in the modulation of LH release [20,21].…”
mentioning
confidence: 99%
“…14 17, 26], rabbit [25], guinea-pig [12], ferret [II], pig [4] and monkey [38] has been shown to influ ence levels of plasma luteinising hormone (LH). We have been studying in the anaesthetised cat the neurophysiology of some of these limbic connections which are involved in the modulation of LH release [20,21].…”
mentioning
confidence: 99%
“…Chronically ovariectomized guinea-pigs are considerably more responsive to a single injection of LH-RH than are the intact animals (Donovan, ter Haar & Parvizi, 1977). Progesterone appears to be of major importance in the control of the length of the guineapig cycle (Donovan & Lockhart, 1972), as it is in many domestic animals; in general, chronic treatment with progesterone tends to reduce the responsiveness of the pituitary gland to LH-RH in most species (for references see Pelletier, 1976), and thus may account for the progressive fall in responsiveness in the guinea-pig as the cycle progresses.…”
Section: Discussionmentioning
confidence: 95%
“…were frequently recorded in association with natural ovulation in conscious animals (Blatchley et al 1976). Anaesthesia might be regarded as having depressed the response, but larger quantities of LH have been released in other work with barbiturate-anaesthetized animals (Donovan et al 1977) while Kilpatrick & Donovan (1981) found that the mean levels of LH in anaesthetized spayed females were higher than in conscious guinea-pigs. The parameters adopted for brain stimulation are considered suitable for the excitation of unmyelinated nerve fibres in the rat (Harris, Manabe & Ruf, 1969), but their applicability to the guinea-pig has not undergone exhaustive tests.…”
Section: Discussionmentioning
confidence: 97%
“…The procedures for electrical stimulation of the hypothalamus and blood collection were employed previously by Donovan, ter Haar & Parvizi (1977). In that study, stimulation of the anterior hypothalamus raised the already elevated plasma concentration of LH in gonadectomized females by about 2-5 ng/ml., although the concentration of FSH was not altered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation